1995
DOI: 10.1111/j.1399-302x.1995.tb00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sonicated material from Fusobacterium nucleatum on the functional capacity of accessory cells derived from dental pulp

Abstract: Fusobacterium nucleatum-derived components were studied for their effect on the ability of accessory pulpal cells to induce T-lymphocyte proliferation. In initial experiments, spleen cells were used to establish concentration ranges at which testing of the effect of the bacterial components would be suitable. At low concentrations, bacterial substances induced a stimulatory effect on the proliferation rate of spleen cells, but not when purified T-lymphocytes were incubated in the presence of concanavalin A and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…For example, sonicated material of Fusobacterium nucleatum can evoke a concentrationdependent stimulatory or suppressive effect on the proliferation rate of accessory cell 14) . Sonicated extract of Actinobacillus actinomycetemcomitans suppressed interleukin-2 production of T-cells 15) .…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…For example, sonicated material of Fusobacterium nucleatum can evoke a concentrationdependent stimulatory or suppressive effect on the proliferation rate of accessory cell 14) . Sonicated extract of Actinobacillus actinomycetemcomitans suppressed interleukin-2 production of T-cells 15) .…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…There are accumulating evidences that pathogenic bacteria associated with endodontic infection and have been shown to alter the host defense system. For example, Yoshida et al 13) reported that sonicated material from Fusobacterium nucleatum can either suppress or stimulate T cell proliferation in the presence of dental pulp accessory cells. Likewise, Gentry-Weeks et al 21) reported that Enterococcus faecalis can survive in mouse peritoneal macrophages.…”
Section: ⅲ Resultsmentioning
confidence: 99%
“…IL-2 stimulates T cells proliferation and involved in cell mediated immunity while IL-4 promotes the B cell to differentiate into plasma cell that produces antibodies and thus mediating humoral immunity 9) . Recent studies [10][11][12][13] have investigated that the suppression of lymphocyte proliferation by pathogenic bacteria related to endodontic treatment failures. Furthermore, Lee et al 14) clearly showed that immunoinhibitory protein extracted from T. denticola suppressed proliferative ability of lymphocytes by arresting cell cycle.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…Bacterial fractions were prepared as previously described 7) . Briefly, bacterial cells harvested from 1-liter cultures were washed, suspended in 20 ㎖ of phosphate-buffered saline (PBS), to minimize the loss of protein, 1 mM of Phenylmethylsul-fonylfluoride (PMSF) were added.…”
Section: Preparation Of Bacterial Sonicated Extractsmentioning
confidence: 99%
“…In previous studies, sonic extracts from bacteria were studied for their effects on the immune response. For example, sonicated material of Fusobacterium nucleatum can evoke a concentration-dependent stimulatory or suppressive effect on the proliferation rate of accessory cell 7) . Sonicated extract of Actinobacillus actinomycetemcomitans suppressed interleukin-2 production of Tcells 8) .…”
Section: ⅰ Introductionmentioning
confidence: 99%